Consideraciones jurídicas y morales sobre la mujer en indias: las “consultas” de Juan De Paz - Rodríguez Arrocha, Belinda (2019)
In this article, the author analyses the activity of colonial institutions in the Philippines during the Spanish period with references to its ethnic particularities. In this sense, the “Consultas y resoluciones varias, teológicas, jurídicas, regulares y morales” (1687) was an illustrative example of work about the judicial and extrajudicial resolution of conflicts in the Philippines under the Habsburgs.In its pages reflects the academic and colonial career of its author, named Juan de Paz. The casuistry and the projection of Thomist thought are two important characteristics of his juridical dissertation. The purpose of this paper is the study of the “Consultas” in regard to his legal, doctrinal and social considerations about women.